1996
DOI: 10.1021/ic950931p
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of Metal-Intercalated Layered Vanadyl Phosphates

Abstract: Variable-temperature magnetic susceptibility shows that electrons on the vanadium centers of the Na+, K+, and Rb+ intercalates of layered vanadyl phosphate are ferromagnetically coupled via V(OPO)2V rings within the layers. The superexchange pathway is preserved in the Sr2+-intercalated system, but antiferromagnetic coupling is observed in the intralayer. This disparate behaviour correlates with the orientation of the basal planes of the (VO)O4 subunits in the X-ray-characterized Rb+-intercalated layered phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 10 publications
4
46
1
Order By: Relevance
“…Yet, the change of the metal cation bears influence on the magnetic interactions, as indicated by different Curie-Weiss temperatures. 60,62,63,64,65 The magnitude of the frustration in the A(VOPO 4 ) 2 · 4H 2 O compounds remains unknown. All the reports available consider NN interactions only.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Yet, the change of the metal cation bears influence on the magnetic interactions, as indicated by different Curie-Weiss temperatures. 60,62,63,64,65 The magnitude of the frustration in the A(VOPO 4 ) 2 · 4H 2 O compounds remains unknown. All the reports available consider NN interactions only.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…[11][12][13][14][15]21] These species are localized in "nests" of the interlayer space. [20] For these materials, the interlayer distances range from 6.30 Å for Ca 2+ to 6.76 Å for Na + .…”
Section: Resultsmentioning
confidence: 99%
“…Lamellar vanadium phosphates are of interest owing to their ability to intercalate organics, [8][9][10] alkali, [11][12][13] alkaline earth metal ions, [14,15] or transition metal (TM) ions. [14,[16][17][18][19] In these compounds, vanadium phosphate layers shift in respect to the adjacent ones with sequences depending on the intercalated species.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of readily reducible V(V) ions in this compound allows for the intercalation of a number of metal ions with the parent layered structure maintained (2). Based on the kind of guest cations, such intercalates which share the stoichiometry M(VOPO ) ) nH O can be classified into two types: (i) monovalent metal intercalates, e.g., M(VOPO ) ) nH O (M"Na, K, Rb; n"3, 4) (3,4), where V> is partially reduced to V>, resulting in mixed-valence compounds; (ii) divalent metal intercalates, e.g., M(VOPO ) ) 4H O (M"Ca, Sr, Pb, Ni, Co, Cu) (5-7), where V> is fully reduced to V>. The divalent transition metal intercalates are principally of interest because of their strong tendencies toward coordination.…”
Section: Layered Vanadyl Phosphate Vopomentioning
confidence: 99%
“…Recently, Papoutsakis et al (4) reported an investigation on the magnetic properties of Na>, K>, Rb>, and Sr> compounds. Conclusions were drawn that the bulk ferromagnetic or antiferromagnetic interactions in these compounds correlate with the orientation of the (VO)O intralayer subunits.…”
Section: Layered Vanadyl Phosphate Vopomentioning
confidence: 99%